Influence of the teacher role on academic performance in primary education - Octavio David Díaz Santana; María-Eugenia Cardenal; Sara María González-Betancor (Humanities & Social Sciences Communications)
Abstract The extant academic literature indicates that both teaching styles and teacher-student relationships exert a significant influence on academic achievement. However, the interrelationship and joint influence of these factors on academic achievement remain underexplored areas of research. This article examines the role of the teacher as a “significant other” in primary education from the perspective of the student. The objectives of this study are threefold: (1) to analyze the relationship between teaching styles and academic achievement, (2) to analyze the relationship between teacher-student relationships and academic achievement, and (3) to determine the influence of the interrelationship between teaching styles and the teacher-student relationships on academic achievement. Structural equation models are estimated with four latent variables: two for the teaching styles (directive and participative) and two for the teacher-student relationships (affective and learning). Student achievement is assessed through the administration of proficiency tests in the following subject areas: Language Communication, English, Mathematics, and Science-Technology. The data presented in this study are derived from a census of 21,126 students in an outermost region of the European Union who were enrolled in the sixth grade of primary education during the 2018/2019 academic year. The findings indicate that the interrelationship between a participative style and teacher-student relationships exerts a positive influence on academic achievement. In contrast, the interrelationship between a directive style and teacher-student relationships has been found to have a negative effect. These findings underscore the influence of social interaction processes within the classroom on academic performance.